Examining the sense and science behind Ghana’s current blanket fertilizer recommendation - Chapoto, Antony; Tetteh, Francis (International Food Policy Research Institute, 2014)
This paper was written to help bolster the case and present visual evidence demonstrating why it is important to seriously consider spatial soil fertility variability in Ghana and to promote area-specific fertilizer recommendations. Using geostatistical analysis of soil samples collected from farmer plots in three districts (Tamale Municipality, Savelugu-Nanton, and West Mamprusi in northern Ghana), the paper analyzes spatial variations in soil fertility. The results clearly show that there are variations in soil pH, organic matter content, and available phosphorous even at the community level, supporting the need for Ghana to seriously consider location-specific fertilizer recommendations.